A Gender-based Stylistic Analysis of Selected English Love Poems - Muhammed, Qaisar Taha; Sharhan, Khalid Sh. (Al-Adab Journal, 2022)
One of the most interesting issues in the study of language is the relation between language and gender. A lot of studies have been conducted so far to find out if men speak and write differently from women. The present study is also an attempt in the same area but it considers gender differences in love poetry. It aims to find out the differences between male and female poets in their love poems. The data of the study consists of three male love poems, and three female poems. Leech and Short's (1981) checklist is used as a framework to analyze the selected love poems. The findings of the study reveal that there are differences between male and female poets with regard to lexical categories, grammatical categories and figures of speech.